Features of Prenatal Diagnosis and Perinatal Management in Patients with Taussig-Bing anomaly - Kurkevych, A. (Ukrainian Journal of Cardiovascular Surgery, 2016)
In the article it was analyzed the perinatal results of diagnosis and treatment of 24 fetuses with Taussig-Bing anomaly from 2006 to 2015. The majority of these patients (90.5%) were born in Kyiv near the cardiac center for consultations of the newborns on the first day of life. The dominant concomitant cardiac anomaly in this group of patients was pathology of the aortic arch (to 57.1%), which only in half of the cases were diagnosed prenatally. Postnatal finding was a high percentage of difficult variants of the coronary arteries courses (63.2%), which increases the risk of cardiac surgery in early neonatal period. Immediate and long-term results of the two-stage surgical treatment of Taussig-Bing anomaly in combination with coarctation or interruption of the aortic arch demonstrated the safety of this method of surgery and low percentage of reoperations (12.5%) in the long-term period.